2018
DOI: 10.1021/acs.jpcc.8b03552
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Water-Based Fracturing Fluids in Kaolinite Slit Pores

Abstract: The adsorption behavior inside kaolinite mesopores of aqueous solutions of various salts and additives is investigated using Molecular Dynamics simulations. In particular, we examine the various combinations of water + salt, water + additive, and water + salt + additive mixtures, where the salts examined are NaCl, CsCl, SrCl2 and RaCl2 and the additives are methanol and citric acid.Citric acid is modeled in two forms, namely fully protonated (H3A) and fully deprotonated (A 3-), the latter being prevalent in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 76 publications
8
36
0
Order By: Relevance
“…We show in Figure 3(c,d) the different behaviour of ions at the two kaolinite faces: the gibbsite face shows a pronounced peak of Cl − anions, and the siloxane face shows a quite smaller peak of the Na + cations and the absence of any Cl − anion in its proximity. Thus, ions distribute on the two kaolinite faces to counteract the intrinsic surface charge, screening the inter-particle Coulomb interaction, in agreement with literature [3,20,25]. This screening effect appears as the reason for the lack of long range interaction among the kaolinite particles in saline solution observed in Figure 3(a).…”
Section: B Short and Long Range Characteristics Of Pmf Profilessupporting
confidence: 88%
“…We show in Figure 3(c,d) the different behaviour of ions at the two kaolinite faces: the gibbsite face shows a pronounced peak of Cl − anions, and the siloxane face shows a quite smaller peak of the Na + cations and the absence of any Cl − anion in its proximity. Thus, ions distribute on the two kaolinite faces to counteract the intrinsic surface charge, screening the inter-particle Coulomb interaction, in agreement with literature [3,20,25]. This screening effect appears as the reason for the lack of long range interaction among the kaolinite particles in saline solution observed in Figure 3(a).…”
Section: B Short and Long Range Characteristics Of Pmf Profilessupporting
confidence: 88%
“…Phyllosilicate kaolinite is composed of a single tetrahedral silicon‐oxygen (siloxane) and an octahedral aluminum‐oxygen (gibbsite) sheets. Several studies have been conducted to investigate the wettability of water/oil droplets on kaolinite surfaces (Papavasileiou et al, ; Siddiqui et al, ; Zhang et al, ). Šolc et al () conducted molecular dynamics simulations to study the wettability of the basal kaolinite.…”
Section: Resultsmentioning
confidence: 99%
“…Clay minerals (e.g., montmorillonite, illite, chlorite, and kaolinite) are ubiquitous and play important roles in both conventional and unconventional reservoirs . Over the last few decades, molecular dynamics (MD) simulations have been extensively employed to study the interactions between organics and clay minerals. Using MD simulations, Underwood and co-workers observed that decane and decanoic acid aggregate together and separate from montmorillonite surfaces by the brine layer covering on montmorillonite surfaces. However, decane and decanoic acid droplets prefer to approach a near kaolinite silicate surface and completely withdraw from the kaolinite hydroxyl surface. , Our previous MD study indicates that the layer charge significantly dominates the wettability of 2:1-type clay .…”
Section: Introductionmentioning
confidence: 99%
“…Anvari and Choi revealed the distribution of water/cyclohexane confined in a 5 nm mesopore composed of kaolinite at different water amounts and salinity, and found that water first covered on the clay surface because of the screening effect of the adsorbed counterions.Papavasileiou et al used MD simulations to examine the adsorption behavior of various aqueous solutions in combination with methanol and citric acids confined in mesopores composed of kaolinite. They found that fully deprotonated citric A 3− tend to aggregate into large clusters driven by cation bridging .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation